Liposome-encapsulated plasmid DNA of telomerase-specific oncolytic adenovirus with stealth effect on the immune system. Issue 1 (December 2017) - Aoyama, Katsuyuki; Kuroda, Shinji; Morihiro, Toshiaki; Kanaya, Nobuhiko; Kubota, Tetsushi; Kakiuchi, Yoshihiko; Kikuchi, Satoru; Nishizaki, Masahiko; Kagawa, Shunsuke; Tazawa, Hiroshi; Fujiwara, Toshiyoshi
Abstract Oncolytic virotherapy has the disadvantage of being unsuitable for systemic delivery due to immune elimination. Liposomal encapsulation is well-recognized to reduce immune elimination and enhance the stability of drugs in the bloodstream. In the present study, the potential of liposome-encapsulated plasmid DNA of telomerase-specific oncolytic adenovirus (TelomeScan) expressing GFP (Lipo-pTS) as an oncolytic adenoviral agent suitable for systemic delivery was investigated. Lipo-pTS, which has a diameter of 40–50 nm, showed potent antitumor effects on HCT116 colon carcinoma cellsin vitro andin vivo . Tumor selectivity of Lipo-pTS was independent of coxsackie and adenovirus receptor (CAR). Importantly, Lipo-pTS reduced production of adenovirus-neutralizing antibodies (AdNAbs) after intravenous administration into immune-competent mice compared to TelomeScan, and even in the presence of AdNAbs, Lipo-pTS maintained strong cytotoxicity. In conclusion, Lipo-pTS has the potential to become an oncolytic adenoviral agent suitable for systemic delivery with the characteristics of CAR-independent antitumor activity and a stealth effect on the immune system.